Body as A Picture Book: A tool for narrative conversations inspired by tattoos - Paul Graham (International Journal of Narrative Therapy and Community Work)
This article introduces a tool for narrative therapy conversations with young people using tattoos as a point of entry. It is inspired by trauma-informed tattooing and discusses how elements of narrative practice can be adjusted to use in conversations about tattoos, whether real or imagined. Narrative practices of externalising, re-authoring, re-membering, the absent but implicit and outsider witnessing are demonstrated. By using a template that invites the person to imagine tattoos or body paint, conversations about tattoos are made available to people who have not been tattooed themselves, including young people.